Cation-exchange synthesis of AgBiS2 and AgBiSe2 quantum dots: A scalable strategy for large-area solar absorbers - Baek, Seungmin; Lee, Young-Ho; Shin, So Jeong; Kwon, Hyo-Geun; Noh, Jae Young; Kim, Jong H.; Kim, Sang-Wook; Kim, Sunghoon (ELSEVIER SCI LTD, 2025)
The cation exchange reaction is the post-treatment process of synthesized colloidal nanocrystals that enables the formation of unique heterostructures as well as facilitates doping, alloying, and other modifications that are typically challenging to achieve through conventional methods. In this work, we synthesized AgBiS2 and AgBiSe2 Quantum dots (QDs), which have emerged as eco-friendly absorbers for solar cell, through the cation exchange method. We incorporated the synthesized quantum dots into solar cells, utilizing aerosol-assisted deposition for the absorption layer. Particularly, we demonstrated that aerosol-assisted deposition (AAD) maintains a uniform film regardless of substrate size and is more advantageous for continuous processes compared to conventional spin coating. To verify this, we deposited films on a large-area substrate and measured the thickness using SEM, evaluating the work function (WF) at various positions to confirm the homogeneous charge transport properties of the deposited films.